STIMULATION OF CREATIVITY IN SCHOOL OF INDUSTRIAL ENGINEERING FOR SOFTWARE DEVELOPMENT AND PRODUCTION - García Z., Teonila (2003)
This article deals with theoretical approaches on software production and development, and with creativity, framed within mankind's constant and accelerated intellectualizing process, leading to form ethicallydeveloped human beings, with both knowledge and lots of creativity.